ANTENA UWB (ULTRA WIDEBAND) MENGGUNAKAN BROADSIDE ARRAY CIRCULAR PATCH 2×2 DENGAN BANDWIDTH 500 MHZ UNTUK RADAR C BAND - M. Reza Hidayat; Andre Yanuar (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2019)
large amounts of data at a fairly close distance with the smallest bandwidth of 500 MHz with a frequency range of 3.1-10.6 GHz which is often applied to WIFI, smartphones and radar, so it is necessary to design an antenna that can produce a wide enough bandwidth. This study made a UWB microstrip antenna with circular patches for c-band radar arranged by a 2 × 2 broadside array using a slot with direct feed technique and is expected to work in the c band frequency range which has a return loss value> 20 dB, VSWR <2, gain > 6 dBi, and bandwidth > 500 MHz. The simulation is carried out using the CST Studio Suite 2019 software by entering antenna parameters based on the results of manual calculations, and optimization is carried out to get the expected antenna specifications.From the final simulation results, it is found that the antenna works at a working frequency of 6.204 - 6,760 GHz with a center frequency of 6.5 GHz, a return loss of 41.1407 dB, a wide bandwidth of 556.1 MHz and a VSWR of 1.0176. Whereas in the measurement results of the circular patch microstrip antenna that have been realized, the antenna works at a frequency of 6,150 - 6,720 GHz with a center frequency of 6,390 GHz, a return loss of 30.62 dB, a bandwidth of 570 MHz, and a VSWR of 1.16.